(untitled) (ItalianoLinguadue, 2021)
L’articolo presenta i risultati dell’analisi di due manuali di italiano LS che sono da tempo presenti sul mercato editoriale russo, ciascuno figlio della propria tradizione glottodidattica, quella russo-sovietica e quella italiana. Si riflette sulle ragioni per le quali il manuale tradizionale russo ha ancora tanto successo tra gli insegnanti di rilievo mentre invece quello italiano, nonostante i suoi numerosi meriti, stenta a diffondersi nelle cattedre più prestigiose. Per l’analisi comparativa è stata elaborata una lista di criteri che, per mancanza di fonti italofone, prende spunto da lavori di autori russi, britannici e polacchi e può essere utilizzata per la valutazione di qualsiasi manuale di lingua straniera. Alla fine dell’articolo si propone una soluzione per poter riconciliare le due tradizioni glottodidattiche in modo che gli studenti russi possano godere pienamente di materiali aggiornati, autentici e altamente motivanti senza dover rinunciare al meglio della tradizione russo-sovietica radicata così profondamente sul territorio nazionale. Traditional language teaching as an obstacle to the renewal of the Italian language teaching in Russia The article summarizes the results of the analysis of two coursebooks for Italian as a foreign language available on the Russian publishing market. One of them was written by a Russian author and represents a quintessence of the Soviet-Russian cognitive comparative approach to teaching foreign languages. The other is a product of a team of Italian experts. We ponder on the reasons why the older Russian textbook is still so successful among teachers of Italian and why it is still difficult to convince them of the need to adopt newer materials and reform the old curricula. A list of criteria was developed in order to carry out a comparative analysis of the two coursebooks. Some works by Russian, British and Polish authors turned out to be useful for the compilation of the list, since there are no works on the subject in Italian. The list could be useful for the evaluation of almost any foreign language textbook. At the end of the article, we propose a solution for reconciliation between the two didactic traditions that could give Russian students a chance to take advantage of modern, authentic and highly motivating materials without the need to abandon the local teaching tradition that is so deeply rooted in Russia.